International survey on plasma transfusion practices in critically ill children. Issue 4 (27th August 2013) - Karam, Oliver; Tucci, Marisa; Lacroix, Jacques; Rimensberger, Peter C.; ,
<x xml:space="preserve">Abstract</x> Background Studies have shown heterogeneity in red blood cell transfusion practices. Although plasma transfusion is common in intensive care, there are no data on plasma transfusion practices in pediatric critical care units. Study Design and Methods A scenario‐based survey was sent to 718 pediatric critical care physicians working in Europe, North America, Australia, and New Zealand. Respondents were asked to report their decisions regarding plasma transfusion practice with respect to four scenarios: pneumonia, septic shock, traumatic brain injury (TBI), and postoperative care after a Tetralogy of Fallot correction. Results The response rate was 187 of 718 (26%); half of the responders worked in North America. The proportion of physicians who transfused plasma to nonbleeding patients, solely based on abnormal international normalized ratio (INR), varied from 66% for pneumonia to 84% for TBI (p < 0.001). In such nonbleeding patients, the median INR threshold that would trigger plasma transfusion was 2.5 for pneumonia and septic shock patients and 2.0 for TBI and the cardiac postoperative patients (p < 0.001). Minor bleeding, minor surgery, insertion of a femoral line, hypotension, abnormal activated partial thromboplastin time, thrombocytopenia, and anemia levels were important determinants of plasma transfusion, whereas none of the respondents' demographic characteristics were important. Conclusion More than two‐thirds of responding pediatric critical care physicians prescribe plasma transfusions for nonbleeding critically ill children. Additionally, there is a significant variation in transfusion practice patterns with respect to plasma transfusion thresholds.